Education and science: current trends - Fedorova I. A., Еремеев А. Д., Batanov M. S., Khachak S. K., Nikolaeva M. A., Zinchik N. S., Bezdudnaia A. G., Danilchenko S. L. (Education and science: current trends, 2017)
the monograph deals with the possibilities of an innovative approach to the vocational training of civil servants, combining traditional and new views, where the phenomena of transforming intelligence, trust, professional culture, world perception and the value orientations of managerial resources enter into in the foreground. These particular components form the basis for the potential of a person's self-development as a manager who thinks and acts in the conditions of rapid changes.
Keywords: ценности; профессиональная подготовка; values; vocational training; государственные служащие; civil servants; социальные изменения; social changes